THE USE OF SEASONAL CHRONOTOPES IN MODERN KARAKALPAK LYRIC POETRY - Zinatdinova G.I. (Researchparks Publishing, 2023)
In this article, the differences in the use of seasonal chronotopes are learned on the example of contemporary Karakalpak lyrics.